Thermo mechanical and morphological interrelationship of polypropylene-multiwalled carbon nanotubes nanocomposites - AR, Jeefferie; MY, Yuhazri; Omar, Nooririnah; MM, Haidir; Sihombing, Haeryip; mohd, salleh; NA, Ibrahim (IJENS, 2010)
In this research, the significance effects of MWCNTs at lower percentage addition in affecting the thermomechanical behavior of the fabricated PP/MWCNTs nanocomposites were studied. PP/MWCNTs nanocomposites were compounded by using the internal mixer, through the simple melt blending technique. The improvement effects of MWCNTs addition were well justified by the transmission electron microscopy (TEM) surface morphological observation. The interrelationships between the TEM surface observations with the thermomechanical results were established by manipulating the three major plots of dynamic mechanical analysis of storage modulus, loss modulus and damping modulus (tanδ). From this work, it was found that the improvement of dynamic thermomechanical properties is directly related to the amount of MWCNTs added and the quality of MWCNTs dispersion within the PP matrix.